Mapping Deep Tech Technologies: Implications for Businesses and Policy Makers - Iavernaro, Fulvio; Capalbo, Enzo; Filitti, Giuseppe (International Journal of Business Management and Finance Research, 2025)
This study provides a comprehensive patent-based analysis of deep tech innovation. Deep tech, encompassing advanced technologies such as artificial intelligence, robotics, quantum computing, and industrial automation, is recognized for its disruptive potential and reliance on intensive scientific research. By analyzing over 138,000 granted patents granted between 2015 and 2025, the study investigates temporal trends, geographical patterns, and key innovation actors. Results reveal a significant rise in deep tech patenting since 2010, with North America leading in patent quality and impact, Asia dominating in volume, and Europe exhibiting a balanced but moderate innovation output. Engineering and Industrial Technologies emerged as the most patent-intensive domain, while Biotechnology and specialized technologies showed the highest impact. The findings highlight the critical role of private firms in driving deep tech innovation and suggest strategic and policy implications for fostering technological leadership, particularly in Europe. This work contributes to the understanding of deep tech as a converging field of general-purpose technologies shaping future innovation ecosystems.